PENGARUH LITERASI KEUANGAN, KONTROL DIRI DAN DOOM SPENDING TERHADAP PERILAKU PENGELOLAAN KEUANGAN MAHASISWA FKIP UNIVERSITAS NUSA CENDANA - MOOY, MARIA ASNAD; YEWANG, MARKUS UMBU KALOLA; HERNAWATI, RETNO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The term 'financial management behavior' describes deliberate financial decision-making, including budgeting, organizing, and using money for daily needs. This study aims to examine how uncontrolled spending, self-control, and financial literacy affect the financial management practices of FKIP UNDANA students. The study uses a quantitative research methodology with an associative qualitative approach. A total of 150 respondents were involved through random sampling. The analysis shows that financial literacy has a partial effect on the financial management behavior of FKIP UNDANA students, self-control has a partial effect, reckless spending has a partial effect, and financial literacy, self-control, and reckless spending all simultaneously affect the financial management behavior of FKIP UNDANA students. It is hoped that this study will serve as a basis for creating financial education materials for students.